PPO.23 Top 15 research priorities for preterm birth with clinicians and service users' involvement – outcomes from a James Lind Alliance priority setting partnership. (9th June 2014) - Uhm, S; Alderdice, F; Chambers, B; Gyte, G; Gale, C; Duley, L; James, CP; David, AL; McNeill, J; Turner, MA; Shennan, A; Deshpande, S; et al.
Abstract : Background: Preterm birth is the single most important determinant of adverse infant outcomes in terms of survival, quality of life, psychosocial and emotional impact on the family, and health care costs. Research agenda in this area has been determined primarily by researchers, and the processes for priority setting in research have often lacked transparency. Objectives: To identify 15 most important priorities for future research for practitioners and service users in the area of preterm birth. Methods: A priority setting partnership was established by involving clinicians, adults who were born preterm, and parents and families with experience of preterm birth. Research uncertainties were gathered from surveys of service users and clinicians, and analyses of systematic reviews and clinical guidance, and then prioritised in a transparent process, using a methodology advocated by the James Lind Alliance. Results: 593 uncertainties were submitted by 386 respondents and 52 were identified from literature reviews. After merging similar questions, a long list of 104 questions were distributed for voting. The 30 most popular items were then prioritised at a workshop. The top 15 research priorities included prevention of preterm birth, management of neonatal infection, necrotising enterocolitis, pain and lung damage, care package at discharge, feeding strategies, pre-eclampsia, emotional and practical support, attachment and bonding, premature rupture of membranes and best time for cord clamping. Conclusions: These top research priorities in preterm birth provide guidance for researchers and funding bodies to ensure that future research addresses questions that are important to both clinicians and service users.